(untitled) (Brazilian Journal of Oceanography, 2019)
Studies involving coastal sediment resuspension have shown that trace metals could be released to the water column due to changes in physical-chemical conditions. Therefore, if environmental agencies adopt screening protocols with insufficient evaluations of contaminant mobilization risks for a given area, the prediction of environmental impacts caused by dredging may be limited. This work evaluates the influence of spatial variation on the geochemical mobility of trace metals (Cd, Cu, Ni, Pb, Zn) after artificial sediment resuspension, using as study case the Iguaçu River estuary (Guanabara Bay, Brazil). The Iguaçu River drains the industrial complex of the metropolitan area of Rio de Janeiro State, besides the presence of agriculture and the input of untreated domestic wastes. Surface estuarine sediments were submitted to resuspension experiments in an open system, during 1h and 24h of agitation on local water. A clear tendency of metals’ solubilization was observed after resuspension, especially considering the dissolved concentrations of Cu (average: 8.0 µg L-1) and Zn (average: 0.9 mg L-1), especially for the samples from the transects 2 and 3. However, evaluations of water quality changes due to sediment resuspension are not requested by the legislation regulating the dredging activities. In the sediments, the results suggested a higher geochemical mobility of Cu, indicated by the massive increase on the bioavailable fraction after resuspension, mainly on the transect number 3, on the river’s mouth. The effects of resuspension were distinct between samples, suggesting that even in a small scale, important differences on metals’ mobility are found. Thus, the combined assessment of changes in metal concentrations in water and in the metal partitioning linked to the solid-phase was demonstrated to be a promising tool for predicting the environmental risks of dredging due to changes in the bioavailability of metals.